Reducing suspension for minor infraction and improving school climate perceptions among black adolescents via cultural socialization: A multi-informant longitudinal study. (August 2022) - Wang, Ming-Te; Scanlon, Christina L.; Del Toro, Juan; McKellar, Sarah E.
Abstract: Racially disparate school disciplinary practices create inequitable circumstances for minority and immigrant youth around the world. In the U.S., Black youth are more likely than their White peers to be suspended for minor, non-violent infractions. This study explores (a) whether school cultural socialization practices reported by Black students ( N  = 544; M age (SD)  = 12.45 (1.57); 49% boys) and teachers ( N  = 38; 84% female) were linked to a reduced likelihood of receiving suspensions for minor infractions and (b) the extent to which Black students' perceptions of school climate mediated this relation. Results indicated that school cultural socialization was linked to a decreased likelihood of being suspended for a minor infraction and improved school climate perceptions for Black students. Black students' perception of school climate mediated the link between school cultural socialization and suspensions for minor infractions. These results highlight school cultural socialization as a promising approach for increasing cultural responsivity and equity within schools, reducing racial bias, and expunging unjust disciplinary responses. Highlights: Concerns about schools' racial diversity climate are widespread. Black youth are more likely than their White peers to be suspended. School cultural socialization was linked to a lower likelihood of being suspended. School climate mediated the link between cultural socialization and suspensions. Educators can reduce disciplinary inequities by implementing cultural socialization.